232k views
3 votes
50 – (12 +9 - 2(3)+2 (1) - 2)

2 Answers

6 votes

Answer:


{ \rm{50 - (12 + 9 - 2(3) + 2(1) - 2)}} \\ \\ = { \rm{50 - 21 + 6 + 2 - 2}} \\ \\ = { \rm{58 - 23}} \\ \\ = { \rm{35}}

User Meolic
by
5.0k points
5 votes

Answer:

35

Explanation:

You have to solve this sum according to BODMAS theory.

That means,

B = brackets

O = of

D = division

M = multiplication

A = addition

S = subtraction

Let us solve now.

50 – (12 +9 - 2(3)+2 (1) - 2)

50 - ( 12 + 9 - 2 × 3 + 2 ×1 -2)

50 - ( 12 + 9 - 6 + 2 -2 )

50 - ( 21 - 6 + 2 - 2 )

50 - ( 15 +2 - 2 )

50 - (17 - 2)

50 - 15

35

User Canni
by
4.3k points